(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the number of comatose patients who requested to go home at Lao Cai provincial General Hospital in 2023, and to describe some characteristics of those patients with coma due to brain injury. Method: A prospective descriptive study involving all patients who met the selection criteria from April 2022 to March 2023 at the Outpatient Department and the Emergency and Intensive Care Unit of Lao Cai provincial General Hospital. Results: From April 2022 to March 2023, Lao Cai provincial General Hospital recorded 60 comatose patients who requested to go home, with an average age of 53 years. Males accounted for the majority (81.7%). Nearly two-thirds were farmers. The Kinh ethnic group represented just over 30%, with the remaining being ethnic minorities such as H’Mông, Thai, Tay, and Dao. Nearly two-thirds had a history of exposure to risk factors such as alcohol, tobacco or drugs. Patients with blood type O had the highest proportion, while only one patient had blood type AB. 50% of the comatose patients who requested to go home had brain injuries, mainly caused by traumatic brain injury due to accidents, cerebral hemorrhage, or cerebral infarction. These patients were mostly male, farmers, with an average age of 49; 90% of them died within 24 hours. Conclusion: In 2023, Lao Cai recorded 60 comatose patients who requested discharge against medical advice; 50% of them suffered brain injuries primarily due to traumatic brain injury from accidents, cerebral hemorrhage, or cerebral infarction, with an average age of 49; 90% of these patients died within 24 hours.